EVALUASI KUALITAS APLIKASI SISTEM INFORMASI MANAJEMEN KEIMIGRASIAN (SIMKIM) VERSI 2.0 BERBASIS WEB MENGGUNAKAN METODE HUMAN ORGANIZATION TECHNOLOGY FIT (Studi Kasus pada Kantor Imigrasi) - Arham Bakri; Anggraeni Ridwan (LPPM, 2021)
Immigration office one of the organization implementing information system integration and automation called the immigration management information system (SIMKIM) Version 2.0 for passport services. An evaluation need to find how the system is implemented, the level of success, as far as to which the system contributes to the organizations that use it. SIMKIM Version 2.0 application have three main component namely human organization and technology. The result of the evaluation indicate technology component include system quality getting value 3,24 (good), information quality getting value 3,09 (good), and service quality getting value 3,21 (good). Human component including system user getting value 3,18 (good), user satisfaction getting value 3,07 (good), and the benefits getting value 3,15 (good), and organization structure getting value 3,22 (good). The overall component SIMKIM Version 2.0 implementation obtained value of 3,16 good interpretation based on HOT Fit method.